Design and development of Phase Change Material (PCM) based hybrid solar dryer for herbs and spices - MANDAL, SILPA; SHARMA, P K; MANI, INDRA; KUSHWAHA, H L; T V, ARUN KUMAR; SARKAR, SUSHEEL (The Indian Journal of Agricultural Sciences, 2020)
Herbs (green leafy plant mass) are highly perishable in nature containing more than 80% moisture. Moisture needs to be removed to less than 11% for storing it for longer period of time. A phase change material (PCM) based solar dryer was developed consisting of collector of area 0.64m2 and three trays of 0.42 m2 of area each in the drying chamber. The dryer consists of a real time data acquisition system for recording the temperature, humidity and moisture loss. Collector was also filled with 20 kg paraffin wax as a latent heat storage material for continuous drying after sunshine. Performance of the developed dryer was evaluated by drying fresh mint and coriander leaves having initial moisture content of 82–86 % ( wb) and compared with developed dryer without PCM and shade drying considering both the drying parameters and quality parameters of the dried herbs. The developed dryer with PCM was found to produce significant difference in drying rate (P<0.0001) for both herbs compared to dryer without PCM and shade drying. All the quality parameters in terms of retention of the total phenolic content and flavonoid, magnesium and iron content found to have significance difference (P<0.0001) compared to without PCM and shade drying. The developed solar dryer provides a promising alternative for continual drying of other materials also including herbs even after sunshine hours with real time data acquisition system and also found to be superior in retaining quality.